Interferometric array planning using division algorithm for radio astronomy applications - Kiehbadroudinezhad, Shahideh (2017)
In order to measure the fine angular detail in the radio frequency range from the sky, two-element interferometers which form radio interferometers and synthesis array are utilized. The angular resolution of a single telescope does not provide sufficient information for astronomy applications, therefore a synthesis array or radio interferometers is used to fulfil the aim of the end users.